Relationships between site characteristics and the productivity in a plantation of Salix nigra located in the Paraná delta (Argentina) - Casaubón, E. A.; Gurini, L. B.; Cueto, G. R. (Forest Systems, 2000)
We studied the quality of forest site in a 6 years old commercial plantation of Salix nigra, located in the Paraná delta (Argentina), which shows a lower productivity than the average in the region. The objective of this study is to identify site components that determine this lower productivity. The environmental factors evaluated were the floristic community, the relief and the edafic factors and their relationship with the height of dominant trees and the site productivity. The lowest height growths were detected in high altitude sites or in plots with the former stratum of soil very wide (with clay-slimy texture), while the best height growths of trees were registered in low altitude sites with a very thin first soil horizon.